Intimacy on display: movie stars, images and everyday life in South India - Gerritsen, Roos (Visual anthropology, 2016)
Because of the close links between the Tamil movie industry and politics, and the position of fans in this, everyday engagements of fans with their actors are generally overlooked. This article focuses on how fandom unfolds in the familial space in Tamil Nadu state, South India. Brothers fight over images, newlywed couples insert movie stars in their wedding photography, and fathers take a son to their favorite star to get him back on the right track. I argue that fandom is inflected in familial relationships as well as being informed by them. Further, I argue that personalized images of movie stars play a crucial role herein.